2021
DOI: 10.3390/ijerph18158060
|View full text |Cite
|
Sign up to set email alerts
|

Life Aspirations, Generativity and Compulsive Buying in University Students

Abstract: The study of goal-oriented behaviour, because of its undeniable repercussions on physical and mental health, is one of the target topics of contemporary research. However, the content of life aspirations, emphasised from the self-determination theory, has received little attention from the field of compulsive buying although it plays an important role in the regulation of behaviour and well-being. Generativity, the personal construct that captures the intentions and/or the need to contribute (leave a legacy) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 104 publications
(156 reference statements)
3
10
0
2
Order By: Relevance
“…In this line, the work by Roberts and Pirog [ 85 ] is particularly relevant: using a sample of university students, a positive association was confirmed between compulsive buying and extrinsic goals in financial success and attractiveness and a negative association with the intrinsic goals of self-acceptance and community feeling. Empirical support to the role played by this motivational unit is also found in other studies conducted using both general population samples [ 51 , 86 ] and university students [ 87 ]. Specifically, Otero-López and Villardefrancos [ 86 ] conclude that it is the people who are more vulnerable to compulsive buying that have the highest scores in the importance given to all extrinsic goals and in the probability of achieving extrinsic image and conformity goals.…”
Section: Level Ii—personal Concerns Characteristic Adaptations and Co...supporting
confidence: 70%
See 2 more Smart Citations
“…In this line, the work by Roberts and Pirog [ 85 ] is particularly relevant: using a sample of university students, a positive association was confirmed between compulsive buying and extrinsic goals in financial success and attractiveness and a negative association with the intrinsic goals of self-acceptance and community feeling. Empirical support to the role played by this motivational unit is also found in other studies conducted using both general population samples [ 51 , 86 ] and university students [ 87 ]. Specifically, Otero-López and Villardefrancos [ 86 ] conclude that it is the people who are more vulnerable to compulsive buying that have the highest scores in the importance given to all extrinsic goals and in the probability of achieving extrinsic image and conformity goals.…”
Section: Level Ii—personal Concerns Characteristic Adaptations and Co...supporting
confidence: 70%
“…They also report the lowest levels in the probability of achieving intrinsic goals. In a later study, these authors [ 51 ] conclude that the extrinsic goals of image, popularity, and conformity strengthen the predictive power of personality traits in compulsive buying; more recently, Otero-López, and Santiago and Castro [ 87 ], confirmed that the life aspirations of image, popularity, and hedonism act as risk factors in compulsive buying, while the importance granted to the intrinsic goals of self-acceptance and affiliation operate as protective factors.…”
Section: Level Ii—personal Concerns Characteristic Adaptations and Co...mentioning
confidence: 96%
See 1 more Smart Citation
“…The total score (ranging from was used as an index of CB tendency. The adequate psychometric properties of the GCBS were confirmed by previous research conducted with Spanish samples [46,47]. In this study, internal consistency was measured using Cronbach s alpha, which was 0.92.…”
Section: Measurements 221 Compulsive Buyingsupporting
confidence: 66%
“…Impulsive shopping tendency refers to a consumer characteristic that leads him/her to undertake the spontaneous, immediate and unreflective purchase of a particular product, and this characteristic is inhibited by the consumer's personality (Verplanken and Sato, 2011). On the other hand, shopping intention represents the consumer conscientiously choosing to spend money on brands that possess the values and ethos and represent the causes aligned with his/her own (Otero-L opez et al, 2021). Chan et al (2017) suggest that consumers develop the urge and motivation before performing impulsive buying.…”
Section: Impulsive Shopping Tendency Shopping Intention and Online Sh...mentioning
confidence: 99%